Combined Pre- and Posttreatment of Paraoxon Exposure - Lorke, Dietrich E; Nurulain, Syed M; Hasan, Mohamed Y; Kuča, Kamil; Petroianu, Georg A (Molecules (Basel, Switzerland), 2020)
AIMS: Organophosphates (OPCs), useful agents as pesticides, also represent a serious health hazard. Standard therapy with atropine and established oxime-type enzyme reactivators is unsatisfactory. Experimental data indicate that superior therapeutic results can be obtained when reversible cholinesterase inhibitors are administered before OPC exposure. Comparing the protective efficacy of five such cholinesterase inhibitors (physostigmine, pyridostigmine, ranitidine, tacrine, or K-27), we observed best protection for the experimental oxime K-27. The present study was undertaken in order to determine if additional administration of K-27 immediately after OPC (paraoxon) exposure can improve the outcome. METHODS: Therapeutic efficacy was assessed in rats by determining the relative risk of death (RR) by Cox survival analysis over a period of 48 h. Animals that received only pretreatment and paraoxon were compared with those that had received pretreatment and paraoxon followed by K-27 immediately after paraoxon exposure. RESULTS: Best protection from paraoxon-induced mortality was observed after pretreatment with physostigmine (RR = 0.30) and K-27 (RR = 0.34). Both substances were significantly more efficacious than tacrine (RR = 0.67), ranitidine (RR = 0.72), and pyridostigmine (RR = 0.76), which were less efficacious but still significantly reduced the RR compared to the no-treatment group (paraoxon only). Additional administration of K-27 immediately after paraoxon exposure (posttreatment) did not further reduce mortality. Statistical analysis between pretreatment before paraoxon exposure alone and pretreatment plus K-27 posttreatment did not show any significant difference for any of the pretreatment regimens. CONCLUSIONS: Best outcome is achieved if physostigmine or K-27 are administered prophylactically before exposure to sublethal paraoxon dosages. Therapeutic outcome is not further improved by additional oxime therapy immediately thereafter.
Keywords: proporcionální rizikové modely; analýza přežití; Cholinesterase Inhibitors; Post-Exposure Prophylaxis; oximes; preexpoziční profylaxe; Male; Rats, Wistar; prophylaxis; Paraoxon; takrin; Proportional Hazards Models; Oximes; mužské pohlaví; Physostigmine; ranitidin; potkani Wistar; rat; cholinesterase; cox analysis; Cholinesterase Reactivators; Survival Analysis; krysa rodu Rattus; pyridostigmin-bromid; organofosfáty; carbamates; Animals; organophosphate; pretreatment; zvířata; Ranitidine; Rats; reaktivátory cholinesterasy; fysostigmin; oximy; Pre-Exposure Prophylaxis; Tacrine; cholinesterasové inhibitory; paraoxon; Pyridostigmine Bromide; Organophosphates; postexpoziční profylaxe